A study of Fajr and Isha prayer times at high latitude regions between 48° to 67° / Siti Asma’ Mohd Nor - Siti Asma’ , Mohd Nor (2016)
Study of prayer times was done at selected high latitude regions. Research is focusing on the night prayer times which is Subh and Isha Prayer times. Study included selected cities locate at 48°N until 67°N latitude. Studies is to ensure the existing way to determine the prayer times at high latitude regions (higher than 48°) can be adopted or need to be adjusted to the alternative way. Thus the existence alternative ways which are nearest latitude, nearest day, middle of night and seventh part of night been discuss in physic perspective. Research is focusing on the standardizing the alternative way. Research covers the perspective of physic (astronomical view) which explains that abnormality in these regions by focusing in the sun‟s altitude. The method used in this research is by using prayer time software Accurate Times and astronomical software which is The Sky Sixth. The used of this software is to simulate prayer time and simulate the sun path. The sun altitude pattern then is analyzed to see the effect of the latitude to the starting of the astronomical twilight and starting of Subh and Isha prayer times. Research finding shows that for cities locate at 48°N until 51°N still could determine starting of Fajr and Isha prayer times by using Accurate Time software. For cities locate above than 51°N until 65° latitude where prayer times undetermined by compute the software thus need to be calculate by alternative way. Research found that by dividing the night by two gives the prayer time start late but gives the more time for the sun to go deeper below horizon where it is most fitted the requirement of fiqh. The changing pattern in the sun‟s altitude will shift the times of prayer.